Hubungan status iodium ibu hamil trimester III dengan status iodium dan nilai antropometri bayi baru lahir di daerah GAKI - Pibriyanti, Kartika; SS, Darmono; Pemayun, Tjokorda Gde Dalem (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background: Iodine essential for thyroid hormone synthesis. Women in their pregnancy are susceptible of Iodine Deficiency Disorder (IDD) since they are facing metabolism and hormonal alteration. IDD in pregnant women gave bad impact to the growth and development of the fetus. Determinant of the life continuity of the newborn babies and their life qualities could be seen through the newborn baby condition based on their body size proportions right after the birth. Objective : Explaining the impact of the iodine status of the pregnant women in their third trimester to the iodine status and anthropometric values of the newborn babies.Method : This research used non experimental study design cross sectional to 52 pregnant women in their third trimester with the babies. The Urinary Excretion of Iodine (UEI) for the examination of iodine status. To the newborn babies, UEI examination and anthropometric measurement, consists of weight birth (WB), length birth (LB), head circumference (HC) were done. Result : There is a significant correlation between the mothers’ UEI and the LB of the newborn babies (p=0,018). There is no significant correlation between mothers’ UEI and the babies’ UEI (p=1,000), mothers’ UEI and the WB of the newborn babies (p=0,548), mothers’ UEI and the newborn babies’ HC (p=0,885).Conclusion : There is a significant correlation iodine status of the pregnant women in their third trimester <150 µg/L with the LB of the newborn babies <48 cm, but there is no significant correlation with the UEI of the newborn babies <100 µg/L, WB <2500 gram, HC<34 cm.